ALTERNATIVE MEDICINE AS AN EFFORT TO CURE DISEASES: REVIEW - Ema Harta Lestari; Amirudin Salem; Umi Hasanah; Nehayatul Sunnah (HEALTH SCIENCES International Journal, 2023)
In modern times, a variety of advanced technologies have been present in various fields, one of which is health. Rapid developments in the health sector include medical care. Medical treatment experiences a lot of progress that gives hope for the patient's recovery. This certainty is because medical treatment has been considered a rational and scientific treatment. On the other hand, in reality, many patients still use alternative medicine. Patients have trust or believe that alternative medicine is a treatment that can heal their illness because they have economical prices, minimal side effects, and are easy to find. The purpose of this literature study is to find out the reasons for patients choosing alternative medicine to heal the disease so that patients choose alternative medicine to try to heal diseases other than using medical treatment.